Pengaruh Rembesan terhadap Stabilitas Keamanan Bendungan Leuwikeris Berdasarkan Parameter Material Timbunan - Hidayat, Muhammad Andhi; Nugraha, Bagus Putra (Riviera Publishing, 2025)
The background of this research is the importance of ensuring the stability of the Leuwikeris Dam, which plays a role in irrigation, raw water supply, and flood control in the Ciamis region, West Java. Fluctuations in reservoir water levels and seepage can affect the stability of dam slopes, so an in-depth analysis of embankment material parameters and earthquake loading conditions is required. The objective of this study is to evaluate the dam's safety factor based on various scenarios, including construction conditions, reservoir filling, and seismic loading (OBE and MDE). The research method involves slope stability modeling using Geo-Studio Slope/W 2023.1.0 software with the limit equilibrium method and dynamic analysis using the Makdisi-Seed method for deformation prediction. The results show that the safety factor meets the criteria under construction and reservoir filling conditions but does not meet the requirements under MDE earthquake loading. However, deformation analysis demonstrated that the maximum displacement (110 cm) remains below the safe limit (368.5 cm). The implications of this study are the need for continuous monitoring and mitigation design to anticipate the risk of major earthquakes, as well as recommendations for optimal fill materials to enhance dam stability.